An intimate distance: women, artists and the body - Betterton, Rosemary.. (Routledge, 1996)
How have women artists taken possession of the female body? What is the relationship between looking and embodiment in art made by women? In a series of original readings of the work of artists from Kathe Kollwitz and Georgia O'Keeffe to Helen Chadwick and Laura Godfrey-Isaacs, Rosemary Betterton explores how women artists have addressed the changing relationship between women, the body and its representation in art. In detailed critical essays that range from the analysis of maternal imagery in the work of German artists at the turn of the century to the unrepresented body in contemporary abstract painting, Betterton argues that women's art practices offer new ways of engaging with our fascinations with and fears about the female body. Reflecting the shift within feminist art over the last decade, An Intimate Distance sets the reinscription of the body within women's art practice in the context of current debates on the body, including reproductive science, maternal subjectivity and the concept of 'body horror' in relation to food, ageing and sex. Drawing on recent theories of embodiment developed within feminist philosophy and psychoanalytic theory, the essays reveal how the permeable boundaries between nature and culture, the female body and technology are being crossed in the work of women artists.
Keywords: 1900-1999; approches et analyses; art contemporain; artistes féministes; arts; corps; cours; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

The art of reflection: women artists'self-portraiture in the twentieth century - Meskimmon, Marsha.. (Columbia University Press, 1996)
Self-portraiture has long been a means for the male artist to assert an identity as masterful creator or tortured soul; women have overwhelmingly been presented as objects, and rarely as subjects of self-portraiture. In recent years, however, women artists have used their work to disrupt this tradition. With 43 illustrations of works by Louise Bourgeois, Frida Kahlo, Alice Neel, Cindy Sherman, and Jo Spence, among others, The Art of Reflection is the first sustained inquiry into the appropriation of self-portraiture by women. In suggestive critical meditations on paintings, photographic work, sculpture, performance art, and body art, Marsha Meskimmon shows how twentieth-century women artists have undermined male-centered definitions of how "the artist" depicts the self. Drawing upon feminist theory and philosophy from Simone de Beauvoir to Luce Irigaray, The Art of Reflection casts doubt on the idea of self-portrait as a mirror, in which the static self is rendered accurately and naturalistically. Meskimmon evokes a series of myths about what an artist is, how "he" should be represented, and how "his" work is to be read as autobiography. Through close readings of the imaginative self-representations of women artists -as male artist and god, as central player in the studio and in the Christian passion- she shatters these myths. In an absorbing assessment of the ways women artists have negotiated the complex group of roles ascribed to "woman," Meskimmon considers the partially nude painting by pregnant artist Paula Modersohn-Becker and performance artist Annie Sprinkle's confrontation of the thin line between celebration of female sexuality and objectification of the female body. As a nuanced appreciation of the interpretations of self-portraiture among women artists, The Art of Reflection will prove an invaluable resource on a subject that has received little attention from art criticism. Meskimmon's work also presents a bold challenge to critical tradition, compelling readers to rethink the meaning of the genre as a whole.
Keywords: 1900-1999; arts; corps; cours; critique d'art; discipline; femmes* artistes; har4600; histoire de l'art; premier cycle; périodes historiques; représentation; thématiques

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques